Air Quality Survey Carried Out by Schoolchildren: An Innovative Tool for Urban Planning - Nali, Cristina; Lorenzini, Giacomo (Environmental monitoring and assessment, 2007)
An educational project on biological monitoring of air quality was launched in 2004 to involve about 650 young students (age 6 to 16) from 21 schools of nine municipalities in Tuscany (Central Italy) in active detection of the crucial pollutant ozone with indicator sensitive tobacco seedlings. Results implied the reading of 9,300 raw biological figures and were fortified by the data captured by six photometric analysers. Under the guidance of their teachers, the students had several opportunities to practice with many basic and applied study areas and were initiated into the scientific method in a simple and absorbing manner. Curiosity and involvement were widespread; a sort of emotional and responsible relationship was developed by several pupils. Though primarily an educational exercise, the survey introduced a research element and the regional picture of air pollution that emerged has increased our knowledge of the air quality situation in the area. Biological monitoring of air quality is a powerful tool to improve the awareness and involvement in key topics of environmental education. In addition, it represents a crucial element for improving the awareness of problems and implies the active participation of citizens in the assessment of several indicators of the state of the environment. Its potential as a robust implement in landscape and urban planning is noteworthy.